The 5' and 3' domains of yeast U6 snRNA: Lsm proteins facilitate binding of Prp24 protein to the U6 telestem region. - Ryan, Daniel E (2002)
The 5' and 3' domains of yeast U6 snRNA contain sequences that are thought to be important for binding to Prp24 and Lsm proteins. By extensive mutational analysis of yeast U6 snRNA, we confirmed that the 3' terminal uridine tract of U6 snRNA is important for U6 binding to Lsm proteins in yeast. Binding of Prp24 protein to U6 RNA is dependent on or is strongly enhanced by U6 binding of Lsm proteins. This supports a model for U6 snRNP assembly in which U6 RNA binds to the Lsm2-8 core prior to binding Prp24 protein. Using compensatory base-pairing analysis, we show that at least half of the recently identified U6 telestem as well as a nucleotide sequence in the other half of the telestem are important for binding of U6 RNA to Prp24 protein. Surprisingly, disruption of base pairing in the unconfirmed half of the telestem enhanced U6-Prp24 binding. Truncation of the entire 3' terminal domain or nearly the entire 5' terminal domain of yeast U6 allowed for detectable levels of splicing to proceed in vitro. In addition to gaining knowledge of the function of the 5' and 3' domains of yeast U6, our results help define the minimal set of requirements for yeast U6 RNA function in splicing. We present a revised secondary structural model of yeast U6 snRNA in free U6 snRNPs.